2012
DOI: 10.1155/2012/492467
|View full text |Cite
|
Sign up to set email alerts
|

An Uncommon Case of Pediatric Neurobrucellosis Associated with Intracranial Hypertension

Abstract: We present the case of a 4-year-old boy who was admitted to hospital with intracranial hypertension, headache, diplopia, papilledema, and a normal brain MRI. Brucella melitensis in the cerebrospinal fluid was confirmed with PCR assay. We believe that neurobrucellosis should be included in the differential diagnosis when headaches persist following brucellosis. In addition, we suggest that when cerebrospinal fluid culture is negative, PCR may prove to be an optimal alternative tool for an immediate and accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…We agree with the comments of Professor Al-Mendalawi regarding the absence of the classical diagnostic findings of neurobrucellosis in the studied patient. However, it has been reported that there are many discrepancies in the diagnostic criteria of neurobrucellosis [11]. We think that this is especially true for paediatric neurobrucellosis.…”
Section: Author Responsementioning
confidence: 86%
See 1 more Smart Citation
“…We agree with the comments of Professor Al-Mendalawi regarding the absence of the classical diagnostic findings of neurobrucellosis in the studied patient. However, it has been reported that there are many discrepancies in the diagnostic criteria of neurobrucellosis [11]. We think that this is especially true for paediatric neurobrucellosis.…”
Section: Author Responsementioning
confidence: 86%
“…Unusual presentations of paediatric neurobrucellosis have been reported including Guillain-Barré syndrome [8,9], epileptic seizures and aggressive mood, intracranial hypertension [10][11][12], acute onset of bilateral blindness [13], visual impairment and unilateral hearing loss [14].…”
Section: Author Responsementioning
confidence: 99%
“…Such patients also may come to remedy with similar symptoms and findings of optic neuritis. 19,20 Therefore, to determine CSF, pressure by lumbar puncture is the rule for definitive diagnosis. Also, LHON should be kept in mind in a patient with vision loss.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] Lymphocytic pleocytosis, decreased glucose level, and elevated protein content are seen in the CSF. [9,10,13] Presumptive diagnosis can be made serologically by Rose Bengal and standard tube agglutination tests. [6] Papilledema occurs in 3% of cases of neurobrucellosis.…”
Section: Discussionmentioning
confidence: 99%